Elimination of visceral leishmaniasis in Ethiopia: cross-sector collaboration and cost sharing to promote sustainability - Duncan Ochol; Kebron Haile; Nathan Onduma; Tsegaye Yohanes; Kimberly Kamara (International Journal of Infectious Diseases)
Objectives: Sustainable elimination of visceral leishmaniasis as a public health problem requires the contribution of various stakeholders led by the governments. An estimation of the contribution of different stakeholders was conducted, focusing on the cost of diagnosis, treatment, and management of visceral leishmaniasis in a hospital setting. The study aimed to estimate the cost of diagnosis, treatment, and management of visceral leishmaniasis in a public hospital in Ethiopia, including the contributions of the government and other stakeholders. Methods: A cross-sectional survey using discharged patients’ data and interviews of health workers responsible for managing visceral leishmaniasis patients was used to estimate the cost of diagnosis and management of visceral leishmaniasis and the proportion of government contribution. Results: Data were collected from 189 patient records and 32 hospital staff. The patients’ mean age was 16.3 years (95% confidence interval: 14.7-17.9). The total cost of diagnosis and treatment of a patient on first-line regimen was US $104.7 and on second-line regimen was US $331.9. The World Health Organization contributions through the provision of diagnostic kits and medicines were US $26.9 and $241.1 per patient on first- and second-line treatments, respectively. The hospital contribution were US $77.8 and US $90.8 per patient on first- and second-line treatments, respectively. The pro-rated monthly medical staff payments ranged from US $93.5 to US $163. The monthly government contributions for diagnosis, treatment, and management were 76% and 29% for patients on first- and second-line treatments, respectively. Conclusions: The contribution by the Ethiopian government of 76% of the cost of diagnosis, treatment, and management of visceral leishmaniasis cases on first-line treatment is significant for the sustainable elimination of visceral leishmaniasis. Further research should be done to investigate the cost effectiveness of integrating visceral leishmaniasis services into the existing health services.